(untitled) (Experimental biology, 2015)
Sites of interaction 686 intronic miRNAs with mRNAs of 51 genes coding intronic miRNAs are established. Peculiarities of interaction of observed miRNAs with mRNAs of each gene in 5’UTR, CDS and 3’UTR are revealed. Appreciable heterogeneity of functional sites of mRNAs on number of sites of linkage miRNAs with mRNAs and on density of locating of these sites is established. Intronic miRNAs differenst by selectivity to mRNAs of certains genes are revealed.